The Phantom Decoy Effect in Perceptual Decision Making. (29th December 2015) - Trueblood, Jennifer S.; Pettibone, Jonathan C.
Abstract: A phantom decoy is an alternative that is superior to another "target" option but is unavailable at the time of choice. In value‐based decisions involving phantom decoys (e.g., consumer choices), individuals often show increased preference for the similar, inferior target option over a non‐dominated competitor alternative. Unlike value‐based decisions that are driven by subjective goals, perceptual decisions typically have an outside criterion that defines the goal of the task (e.g., target is present or absent). Despite their obvious differences, past research has documented a number of commonalities between both types of decisions. In a set of three experiments, we examine the influence of phantom options on simple perceptual decisions and point out a critical difference between perceptual and value‐based decisions. Our results show that in perceptual choice, participants prefer competitor options to target options, the opposite of the pattern typically found in consumer choice. We use the results of the experiments to examine the predictions of four different models of context effects including loss aversion and dynamic, preference accumulation models. We find that accumulation models provide the best explanation for our results as well as being able to generalize to other context effects. Copyright © 2015 John Wiley & Sons, Ltd.